TTLL4 mediates the PI3K/AKT/MDM2 pathway to promote hepatocellular carcinoma progression and predict patient prognosis - Zeping He; Desheng Chen; Lei Li; Shanbao Li; Fangbin Song; Jinfeng Cai; Xueyan Guo; Yaohao Luo; Xinshuai Wang; Zeping Chen; Junming Xu (APL Bioengineering)
Hepatocellular carcinoma (HCC) is a highly lethal and heterogeneous tumor driven by the dysregulation of multiple genes. Tubulin tyrosine ligase-like 4 (TTLL4) has been linked to tumor progression, but its specific role in HCC pathogenesis remains unclear. RNA sequencing data, somatic mutation profiles, and clinical characteristics were analyzed from TCGA, GEO, and TIMER databases. The effects of TTLL4 on cell proliferation, migration, and apoptosis were studied using functional assays and flow cytometry. In vivo, tumor growth and metastasis were evaluated through subcutaneous implantation and tail vein injection. Immunohistochemistry assessed TTLL4 and Ki-67 expression. TTLL4 was upregulated in HCC and associated with poor prognosis, linking it to cancer progression and the PI3K–AKT signaling pathway. Knockdown of TTLL4 in HCC cells reduced proliferation, migration, and colony formation while increasing apoptosis. In vivo, TTLL4 knockdown slowed tumor growth and reduced lung metastasis. It also decreased the expression of proteins in the PI3K/AKT/MDM2 pathway, while overexpression upregulated these proteins. Rescue experiments further suggest that TTLL4 may exert its regulatory effects on this pathway by modulating PI3K expression levels. TTLL4 plays a significant role in HCC progression via the PI3K/AKT/MDM2 pathway and may serve as a novel therapeutic target for HCC diagnosis and treatment.